Net primary productivity of Betula platyphylla woodland and the response of current-year shoots to vegetation degradation in Mongolian forest steppe - Demidkhorloo Bayarsaikhan; Buho Hoshino; Takashi S. Kohyama; Shin-ichiro Aiba (Journal of Asia-Pacific Biodiversity)
At the southern margin of forest steppe vegetation in Mongolia, Betula platyphylla woodlands occur on north-facing slopes and hilltops, where congeneric shrub Betula fusca often coexists. Woodland degradation results in B. fusca scrub with scattered B. platyphylla trees. We studied the structure and productivity of a B. platyphylla woodland and the current-year shoot allometry in the Hustai National Park of central Mongolia. For the B. platyphylla woodland examined, stand basal area and estimated aboveground biomass for stems ≥ 3 cm diameter were 3.9 m2 ha–1 and 13.3 Mg dry mass ha–1, respectively. Leaf area index was 0.93 indicating open canopy layer. Aboveground net primary productivity as the sum of coarse wood production and current-year shoot mass amounted to 1.89 Mg dry mass ha–1 year–1, which was high relative to small aboveground biomass. Analysis of current-year shoot allometry demonstrated that B. platyphylla had more xeromorphic shoots in the scrub, with smaller specific leaf area, lower mass ratio of leaf laminae to supporting parts, and smaller lamina mass against the sum of petiole basal area, than in the woodland. Our results indicate that current-year shoot allometry characterizes tree response to woodland degradation at the dry margin of forest steppe.